Studying the Immediate Effects of Two Types of Thumb Splints on the Pain, Grip Strength, and Hand Function in People With De Quervain Tenosynovitis - Hanieh Mohammadzadeh; Abolghasem Zarezadeh; Mohammad Ali Mardani; Ebrahim Sadeghi-Demneh (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective: The prevention of thumb joints flexion help cure de Quervain tenosynovitis. The thumb, therefore, is being immobilized in the abduction position by splinting. Thumb abduction can be away from the palm (palmar abduction) or from the fingers (radial abduction), which are done in two different planes. To the authors' knowledge, the literature has not specified which kind of thumb abduction has better treatment outcomes and functions. This study aimed to compare the immediate efficacy of palmar abduction and radial abduction splinting on the severity of pain, handgrip, palmar and lateral pinch strength, and hand function in people with de Quervain tenosynovitis. Materials & Methods: In this quasi-experimental study, 30 volunteer patients (24 females) with de Quervain tenosynovitis referred to clinical centers were selected via convenience sampling. The participants were randomly assigned to three study groups (without the splint, palmar abduction splint, and radial abduction splint). The splints' height was two-thirds of the elbow. The splints were designed to immobilize the carpometacarpal and metacarpophalangeal joint of the thumb but allow the interphalangeal joint to move. One splint immobilizes the thumb in palmar abduction, while another immobilizes the thumb in radial abduction. The outcomes were studied and measured immediately after the intervention and in a single session. The intended outcomes included pain severity, handgrip strength, palmar and lateral pinch strength, and hand function measured with a visual analog scale, hand dynamometers, and the Jebsen-Taylor test, respectively. The repeated measures analysis of variance was performed for statistical analysis using SPSS software, version 16. Results: All participants completed all study assessments. The results showed a significant reduction of pain, handgrip strength, lateral and palmar pinch, and hand function after using a thumb splint compared to without the splint condition (P<0.05). The pain severity in gripping objects was lower after using a palmar abduction splint than the radial abduction splint. Also, the strength reduction in taking objects by gripping, lateral pinch, and palmar was lower after using the palmar abduction splint than the radial abduction splint (P<0.05). Still, both splints were not significantly different in slowing the hand function in the Jebsen-Taylor test (P>0.05). Conclusion: The positioning of the thumb in palmar abduction with splinting could be more effective for pain reduction and manipulation of objects with the hand and fingers.